Analisis Hukum Islam dan Peraturan Menteri Sosial terhadap Program Bantuan Pangan Non Tunai - Sofura Alfia Dayana; Zaini Abdul Malik (Jurnal Riset Perbankan Syariah, 2023)
Abstract. Non-Cash Food Assistance is food social assistance from the government to reduce the burden by fulfilling some food needs. The objectives of this research are: (1) Knowing the implementation of the distribution of the BPNT program in Bencoy Village. (2) Knowing the analysis of Islamic law principles and the Minister of Social Affairs Regulation No. 5 of 2021. This research method uses a qualitative research type with a normative juridical approach. The research data were obtained from the object to be examined by carrying out observations, interviews, questionnaires, documentation and literature studies. Based on the research results, it was found that the distribution of the Bencoy Village Non-Cash Food Assistance (BPNT) program was channeled in cash through the Post Office, the assistance funds provided by the government were required to spend on food. According to Minister of Social Affairs Regulation No. 5 of 2021, the use of funds received by Beneficiary Families (KPM) is not fully in accordance with existing regulations. In terms of the principles of Islamic law and muamalah, they are not fully in accordance with the principles of trustworthiness and the principles of honesty. Abatrak. Bantuan Pangan Non Tunai merupakan bantuan sosial pangan dari pemerintah untuk mengurangi beban melalui pemenuhan sebagian kebutuhan pangan. Tujuan dalam penelitian ini adalah, (1) Mengetahui pelaksanaan penyaluran program BPNT di Desa Bencoy.(2) Mengetahui analisis prinsip hukum Islam dan Peraturan Menteri Sosial no 5 tahun 2021. Metode Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan yuridis normatif. Data penelitian diperoleh dari objek yang akan diteliti dengan melaksanakan observasi, wawancara, kuesioner, dokumentasi dan studi literatur. Berdasarkan hasil penelitian yang diperoleh bahwa penyaluran program Bantuan Pangan Non Tunai (BPNT) Desa Bencoy disalurkan secara tunai melalui Kantor Pos, dana bantuan yang diberikan pemerintah diharuskan untuk membelanjakan bahan pangan. Menurut Peraturan Menteri Sosial no 5 tahun 2021 dalam penggunaan dana yang diterima Keluarga Penerima Manfaat (KPM) belum sepenuhnya sesuai dengan regulasi yang ada. Dilihat dari segi prinsip hukum Islam dan muamalah belum sepenuhnya sesuai dengan prinsip amanah dan prinsip kejujuran.